The Peroxidative Changes in Rat Brain Tissue Homogenates by Vitamin C and Deferoxamine against Vanadium-Stimulated Lipid Peroxidation - El-Shaari, Fatum A.; Haider, Syed Saleem; M-El-Fakhri, Rehab (Libyan International Medical University Journal, 2023)
Objectives Vanadium (V) metal induces lipid peroxidation (LPO) and this has been proposed as a cause for its neurotoxicity.Aim This study aimed to evaluate the effects of vitamin C (VC) and deferoxamine (DF) against V-induced LPO in brain tissue homogenates in vitro.Methods Male Sprague-Dawley rats were used. Brains were removed and dissected into hypothalamus, hippocampus, brain stem, and medulla pons. They were homogenized in150mM potassium chloride (KCl), and incubated for 1 hour with V, VC, and DF in a micromolar concentration of 20 and 100. Aliquots were used for the estimation of LPO in spectrophotometer. Data analysis were done by one-way analysis of variance.Results V exposure (20 and 100μM) demonstrated statistically significant (p < 0.001) enhancement of LPO (average increase with 20μMV was by +105% and with 100μMV was by +130%), respectively, in brain tissue homogenates compared with water controls. Hypothalamus exhibited maximum enhancement (average increase with 20μMV was by +145% and with 100μMV was by +175%, respectively), in LPO than other regions. Coexposure of brain tissue homogenates to V + VC (20 and 100μM) further accelerated the LPO (+24% and +16%, respectively) compared with V alone. Brain stem exhibited highest increases (+54% with 20μMV and +21% with 100μMV; p < 0.001), respectively. V-induced oxidative consequences were remarkably inhibited (average -55%; p < 0.001) by DF + V (20μM + 100μM) exposure. Hypothalamus and medulla pons exhibited inhibition, by −66% and −60% (p < 0.001) respectively.Conclusion V exposure in vitro resulted in oxidative damage with significant regional variations in brain tissue homogenates. VC is pro-oxidative in vitro reactions and DF chelates V-ion moiety.
Keywords: brain tissues; deferoxamine; homogenates; lipid peroxidation; vanadium; vitamin C